Principles of marketing a global perspective - Kotler, Philip; Armstrong, Gary (Gary M.); Ang, Swee Hoon; Leong, Siew Meng; Tan, Chin Tiong; Yau, Oliver Hon-Ming (Pearson, 2009)
Marketing has gotten more global, and there is a need to develop marketers who understand marketing in the right context. Principles of Marketing: A Global Perspective seeks to do just that by exposing your students to a wide variety of contexts whether international or from within Asia that are presented in the cases, examples and vignettes. To help students to better relate what they are learning to their daily lives, examples comprising recognizable brand names and companies are used. Together with the use of strong visuals, students will find the text an exciting read motivating and creating in them an interest in marketing. At the same time, non-native speaking Asian students will appreciate the concise language and visual learning aids included to help them grasp marketing concepts easily. To encourage students to stay abreast of latest developments in marketing, Principles of Marketing: A Global Perspective provides a good coverage of contemporary marketing issues like the use of technology in marketing and marketing ethics. New Features with Great Benefits and Advantages In this edition, you will find that we have: Selected a good mix of international and Asian cases and vignettes Made the text more concise and used visual aids to make learning easier. Refreshed our coverage of contemporary marketing with new and updated materials 1) A good mix of international and Asian cases and vignettes 2) Concise with Engaging Visuals Principles of Marketing: A Global Perspective makes learning from the text easier for Asian students, who are non-native speakers of English. The effective use of visual learning aids also enables students to obtain a firm grasp of concepts quickly and is an attractive tool for revision. 3) Coverage on Contemporary Marketing Issues Keep your students at the front of the pack! In today s globally-connected world, it is important for them to keep abreast of must-know marketing issues and be critical thinkers of how these affect them.